Malaria epidemics in Europe after the First World War: the early stages of an international approach to the control of the disease Malária epidêmica na Europa após a Primeira Guerra Mundial: estágios iniciais de uma abordagem internacional de controle da doença - Gabriel Gachelin; Annick Opinel (História, Ciências, Saúde: Manguinhos, 2011)
The severity and endemicity of malaria declined gradually in Europe until WWI. During and after the war, the number of malaria cases increased substantially and peaked in 1922-1924. This prompted the Hygiene Commission of the League of Nations to establish a Malaria Commission in 1923 to define the most efficient anti-malaria procedures. Additionally, between 1924 and 1930 there were several international meetings and collaborations concerning malaria, which involved the main institutes of parasitology and the Rockefeller Foundation. The Commission reports, the guidelines for anti-malaria campaigns and the scientific programs which came out of these meetings and collaborations are analyzed in the present paper. Antes da Segunda Guerra Mundial, a severidade e endemicidade da malária diminuíram gradualmente na Europa. Durante e após a guerra, o número de casos cresceu substancialmente, chegando ao máximo entre 1922 e 1924. Isso fez com que a Comissão de Higiene da Liga das Nações estabelecesse, em 1923, a Comissão de Malária, para definir procedimentos mais eficazes contra a doença. Entre 1924 e 1930 encontros e colaborações internacionais, nos quais estiveram envolvidos os principais intitutos de parasitologia e a Fundação Rockefeller, discutiram a enfermidade. Os relatórios da Comissão, as diretrizes para campanhas antimaláricas e os programas científicos decorrentes desses encontros e colaborações são analisados no artigo.